al-‘Alāqah bayna Ṭarīqah al-Ghinā’ bi-Diqqati Nuṭq al-Ḥurūf fī Ta‘allum al-Lughah al-‘Arabiyyah li-Ṭālibāt Markaz al-Lughah al-‘Arabiyyah bi-Ma‘had "Wālī Sughū" Cukir Jombang - Meryl Novi Therisa; Muhammad Arif Setyabudi; Chusnia Rahmawati (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2022)
This research is determined on the knowledge of the relationship between the singing method and the pronunciation of letters in learning Arabic for students from the Arabic Language Center, Walisongo, Cukir, Jombang. And the research curve of this study is: researchers used here as a quantitative curve. Methods of collecting data by testing, questionnaires, and risks. As for the search results, we can see the following: (1) Applying the singing method in the Arabic language center by using vocabulary songs (2) the accuracy of the pronunciation of letters in learning Arabic is the accuracy of the students in speaking Arabic (3) the relationship between the methods singing with the accuracy of the pronunciation of letters in learning Arabic is 0.710. This value is 0.05 So H0 accept and Ha is rejected.